Control of Rotor-Blade Coupled Vibrations Using Shaft-Based Actuation - René Hardam Christensen; Ilmar Ferreira Santos (Shock and Vibration)
When implementing active control into bladed rotating machines aiming at reducing blade vibrations, it can be shown that blade as well as rotor vibrations can in fact be controlled by the use of only shaft-based actuation. Thus the blades have to be deliberately mistuned. This paper investigates the dynamical characteristics of a mistuned bladed rotor and shows how, why and when a bladed rotor becomes controllable and observable if properly mistuned. As part of such investigation modal controllability and observability of a tuned as well as a mistuned coupled rotor-blade system are analysed. The dependency of the controllability and observability on varying rotational speed and mode shape interaction phenomena between parametric and basis mode shape components are also analysed. Numerical results reveal a limitation of the achievable controllability and observability, once quantitative measures of modal controllability and observability converge toward steady levels as the degree of mistuning is increased. Finally, experimental control results are presented to prove the theoretical conclusions and to show the feasibility of controlling rotor and blade vibrations by means of shaft-based actuation in practice.